The MASCC Textbook of Cancer Supportive Care and Survivorship - Olver, Ian (Springer US : Imprint: Springer, 2011)
Addressing physical and psychosocial matters of survivorship prior to, during, and after anticancer treatment is central to a patient's wellbeing. The MASCC Textbook of Cancer Supportive Care and Survivorship explores not only the diagnosis and treatment but also the increasingly recognized complex and ongoing symptoms experienced by long term cancer survivors. Significant advances have been made, designing strategies to manage the side effects and symptoms of treatment and to prevent them from occurring, maximizing the person's ability to pursue daily activities. The MASCC Textbook of Cancer Supportive Care and Survivorship assembles international, multidisciplinary experts who focus on a comprehensive range of symptoms and side effects associated with cancer and its treatment. Intended for health professionals involved with cancer care, medical oncologists, radiation oncologists, surgeons, general practitioners, nurses and allied health workers, this textbook provides current information on the management and prevention of cancer related side effects, referring to up-to-date sources that are useful for conducting further research.